IIIF report : through tangibility enriched : getting started with IIIF and linked open data technology for heritage workers - Veramme, Sofie (Ghent: Amsab-Institute of Social History, 2021)
"Publicatie naar aanleiding van het project A world of diamond: diamond workers in Belgium, the Netherlands and France, 1895-2000 FULL TEXT AVAILABLE AT AMSAB-ISH"